A study on the most contributed factor that encourage to the development of students’ soft skills in Malaysia Institute Information Technology, University of Kuala Lumpur (UniKL) / Mohamad Zikri Emir Ramli - Ramli, Mohamad Zikri Emir (Faculty of Administrative Science and Policy Studies, 2014)
Regardless of graduates’ field of study, soft skills are vital for them to acquire. These skills such as communication skills, analytical, critical and problem solving skills, lifelong learning ability, entrepreneurship and management skills are the ones that employers value as important skills for potential employees to possess. For instance, Madden (2007) stresses those good communication skills have never been more important for chartered accountants. He adds that while the technical skills of accountancy are vital, the need for “soft skills” is just as relevant to the job. Moreover, soft skills are important for Information Technology graduates as they are, most of the time, given the task of project management due to their expertise in the development and installation of information systems (Hairuzila Idrus, 2005). Research suggests that soft skills are just as good an indicator of job performance as traditional job qualifications or hard skills. One study, for example, by The Protocol School of Washington, DC and conducted by Harvard University, the Carnegie Foundation, and the Stanford Research Institute has shown that technical skills and knowledge account for about 15 percent of the reason an individual gets a job, keeps the job and advances in that job (Crosbie, 2005).